THE INFLUENCE OF GROUND TIME TO DOMESTIC FLIGHTS TOWARD FLIGHT DEPARTURE TIME - Zita Habsari, Erlina; Rochmawati, Laila; Muti Sazali, Abdul; Agus Furyanto, Faoyan (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Sultan Aji Muhammad Sulaiman Sepinggan Airport in Balikpapan is one of the busiest airports on the island of Kalimantan, connecting airports in central Indonesia. Domestic aircraft activity at this airport decreased after the Covid- 19 pandemic. Give each airline enough time to prepare for the next flight to depart. Ground time refers to the aircraft that has been grounded. Too much time on the ground will delay flight departure. This study aims to determine the effect of ground time on the punctuality of flight departures. Research techniques used quantitative research methods and data from literature reviews, linear regression analysis and interviews. The authors' findings suggest that the ground time of Indonesian airlines has an effect on flight departure speeds at Sultan Aji Muhammad Sulaiman Sepinggan Airport in Balikpapan. The t-test's t-count is 2,527, which is higher than the t-table's 2.3060, indicating that ground time has a significant effect on on-time departures. In the coefficient of determination test, variable Y explained 51.5% of the variable X, the remaining 48.5% could not be explained by other independent variables. Ground weather variables such as aircraft type, weather conditions, staff activity, and aircraft capacity also have an impact. Discuss optimization of trucking operations